Spatiotemporal cytokinin response imaging and ISOPENTENYLTRANSFERASE 3 function in Medicago nodule development. Issue 1 (21st September 2021) - Triozzi, Paolo M; Irving, Thomas B; Schmidt, Henry W; Keyser, Zachary P; Chakraborty, Sanhita; Balmant, Kelly; Pereira, Wendell J; Dervinis, Christopher; Mysore, Kirankumar S; Wen, Jiangqi; Ané, Jean-Michel; Kirst, Matias; et al.
Abstract: Most legumes can establish a symbiotic association with soil rhizobia that trigger the development of root nodules. These nodules host the rhizobia and allow them to fix nitrogen efficiently. The perception of bacterial lipo-chitooligosaccharides (LCOs) in the epidermis initiates a signaling cascade that allows rhizobial intracellular infection in the root and de-differentiation and activation of cell division that gives rise to the nodule. Thus, nodule organogenesis and rhizobial infection need to be coupled in space and time for successful nodulation. The plant hormone cytokinin (CK) contributes to the coordination of this process, acting as an essential positive regulator of nodule organogenesis. However, the temporal regulation of tissue-specific CK signaling and biosynthesis in response to LCOs or Sinorhizobium meliloti inoculation in Medicago truncatula remains poorly understood. In this study, using a fluorescence-based CK sensor ( pTCSn::nls:tGFP ), we performed a high-resolution tissue-specific temporal characterization of the sequential activation of CK response during root infection and nodule development in M. truncatula after inoculation with S. meliloti . Loss-of-function mutants of the CK-biosynthetic gene ISOPENTENYLTRANSFERASE 3 ( IPT3 ) showed impairment of nodulation, suggesting that IPT3 is required for nodule development in M. truncatula . Simultaneous live imaging of pIPT3::nls:tdTOMATO and the CK sensor showed that IPT3 induction in the pericycle at the base of nodule primordium contributes to CK biosynthesis, which in turn promotes expression of positive regulators of nodule organogenesis in M. truncatula . Abstract : Precise spatial and temporal characterization of cytokinin (CK) responses reveals the function of the CK biosynthesis gene ISOPENTENYLTRANSFERASE 3 during nodule development in Medicago truncatula.